An Experimental Comparison of Selected Blue Flame Pyrotechnics. Issue 1 (25th November 2020) - Juknelevicius, Dominykas; Hahma, Arno; Webb, Rutger; Klapötke, Thomas M.; Ramanavicius, Arunas
Abstract: In this research, 10 different pyrotechnic blue flame compositions were designed and compared. Chromaticity and luminosity parameters of the flame were measured using Ocean Optics JAZ‐ULM VIS‐Spectrometer equipped with a cosine corrector. Color saturation, luminous intensity, specific luminous intensity, oxygen balance, burn rate, actual and theoretical maximum density, color coordinates (X, Y) are presented and discussed. Abstract :